EKSISTENSI KORAN CETAK DI TENGAH DIGITALISASI MEDIA PADA DUA PERUSAHAAN KORAN DI PEKANBARU - Dzikrul Nahla Hutama; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research was conducted at two newspaper companies located in the city of Pekanbaru, namely Riau Pos and Haluan Riau, to know the existence of printed newspapers in the era of digitalization of media as it is today by reviewing their printed newspaper production activities in today's digital era, as well as looking for know how their distribution methods work so that they can survive in facing the challenges of digitalization of media. To answer the formulation of the problem, qualitative methods are used with data collection techniques in the form of in-depth interviews, observation, and documentation coupled with a simple survey to strengthen data regarding the existence of printed newspapers in the present. The subjects in this study were two representatives from each newspaper company and three newspaper sellers in the city of Pekanbaru as triangulation subjects. The results of this study note that the circulation of printed newspapers in Pekanbaru City is now greatly reduced because the amount of production has also been greatly reduced, this is because people are more interested in accessing news and seeking information through online media. With the presence and rise of online media, companies experience disruption which then requires them to transform their media production from print to online. To answer this problem, they are innovating to create a new platform for online media so that they can survive and maintain the market. Nevertheless, even though the production and circulation of printed newspapers have now greatly decreased, printed newspapers are still the choice of some people because newspapers are considered to have a higher level of trust than online media which often contains hoax news. Thus, newspaper companies will still be able to survive and exist as long as the community still needs them. Keywords: Newspaper, Digitalitation, Transformation of Technology